Icariin: Can an herbal extract enhance dental implant outcomes? - Qiang Wang; Xiaoying Wang; Xin Xu (Wolters Kluwer Medknow Publications, 2012)
Introduction: The success rate of dental implant is closely related to three aspects including supporting bone before implantation, osseointegration process, and prevention of peri-implantitis after implantation. Icariin is one of the traditional Chinese herbal medicines to treat impotence, improve sexual function, and enhance immune function. Recently, there are abundant evidences showing that icariin can strengthen bones, enhance bone healing, inhibit osteopenia, and inhibit inflammation. The Hypothesis: We hypothesize that Icariin may be applied clinically to strengthen and accelerate osseointegration of dental implants, inhibit the peri-implantitis, and shorten the rehabilitation time. Evaluation of the Hypothesis: Limited success has been achieved to help implant surgery in spite of much effort. The application of icariin might be a potential method to improve the success rate of dental implant, contributing greatly to implant dentistry.